EVALUASI KEBIJAKAN PEMERINTAH KOTA DUMAI DALAM PELAKSANAAN PENGENDALIAN PENCEMARAN LINGKUNGAN DI KAWASAN PELABUHAN INDONESIA 1 CABANG DUMAI TAHUN 2022 - Desvebiola, Sahira (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Dumai City is known as an oil city and the largest oil industry export port in the country. Dumai, which is the center of Crude Palm Oil (CPO) production, makes its area the location of industrial factories. The Indonesia Port Branch of Dumai is a special area where 13 industrial companies engaged in CPO processing are located. The purpose of the production activities from this industry is to bring benefits to the community by providing job opportunities. However, the existence of this industry also brings negative impacts in the form of environmental pollution, thus requiring a policy for controlling the environmental pollution that occurs. This study aims to evaluate the policy on environmental pollution control issued by the Dumai City Government, specifically the Dumai City Environmental Agency. Method: This research uses a qualitative research method with a descriptive research design. Data collection was carried out by conducting interviews, observations, and documentation. Results/Findings: The results of the research analyzed using the evaluation theory from Bridgman & Davis which includes 4 indicators namely input, process, output, and outcome show that the policy on environmental pollution control in the Indonesia Port Branch area of Dumai has not been fully implemented due to obstacles in one of the indicators, namely the input indicator. Conclusion: The obstacle is the lack of human resources and infrastructure both in terms of quality and quantity. Therefore, efforts are needed to overcome this by improving the quantity and quality of supporting resources at the Dumai City Environmental Agency. Keywords: Policy evaluation, Control, Environmental Pollution